KRAS mutated Non‐Small Lung Carcinoma: A Real World Context from the Indian subcontinent. (7th September 2022) - Batra, Ullas; Nathany, Shrinidhi; Sharma, Mansi; BP, Amrith; Jose, Joslia T.; Singh, Harkirat; Mattoo, Sakshi; Mehta, Anurag
Abstract: Background: KRAS, although a common variant of occurrence ( 20% of non‐small‐cell lung carcinoma [NSCLC]) has been untargetable, owing to the molecular structure which inherently prevents drug binding. KRAS mutations in NSCLC are associated with distinct clinical profiles including smokers and mucinous histology. KRAS G12C mutations account for 40% KRAS altered NSCLC, but NSCLC being a geographically diverse disease, the features may be distinct in this part of the world. This is a single‐center experience of KRAS ‐mutated NSCLC including clinical, imaging, pathologic features, and treatment patterns and outcomes. Methods: This is a single‐center retrospective study of KRAS‐mutated NSCLC. The clinicopathological features and outcomes were retrieved and collated from the medical record archives of the hospital. Results: Fifty (30.6%) patients with advanced‐stage NSCLC with alterations in the KRAS gene were enrolled in the 163 patients who were tested for KRAS alterations. The median age was 61 years. Molecular detection revealed three main types of KRAS mutations viz‐a‐vis: G12C in 17 (34%), G12V in 9 (18%), and G12D in 6 (12%) patients. Comparing G12C versus the non‐G12C mutated cases, co‐mutations were common in the non‐G12C subgroup ( p < 0.05). Among the 36, who were treated at our center, all received chemotherapy as the first line with a median progression‐free survival (PFS)of 5.4 months. The PFS of G12C was higher than the non‐G12C subgroup (6.4 vs 3.8 months). Conclusion: This is the largest single‐center experience from the Indian subcontinent for KRAS‐mutated NSCLC with distinct clinical features. It highlights the unmet need for G12C inhibitors in our country, where prevalence is equivalent to the West. Abstract : Real world study depicting prevalence of KRAS mutated NSCLC (30.6%) in India with G12C seen in 34% cases. Co‐mutations were higher in non G12C subgroup (p<0.05), and the PFS with chemotherapy was longer in G12C subgroup (6.4 months vs. 3.8 months).